An Overview of Partner Choice for Early Adult Women who Experience Fatherlessness in Orphanages - Lisna Putri Kristina Lumban Tobing; Ervina Marimbun Rosmaida Siahaan (Cita konsultindo, 2024)
Everyone is constantly developing, starting from infancy, adolescence, and adulthood. As we enter the early adult stage, one of our developmental responsibilities is to begin a new role as a partner, which involves choosing a partner. The choice of a partner is generally associated with a father figure who will be a role model in choosing a partner. Every daughter needs a father figure, but not all girls can experience this due to the physical and psychological absence of a father, a condition known as fatherlessness. This study aims to describe the partner selection process among early adult women who have experienced fatherlessness in orphanages. Respondents in this study were early adult women aged 18–25 who already had a partner. The study employed a qualitative research method, incorporating a phenomenological approach. Data collection methods include semi-structured interviews. Respondents in this study totaled two people. The data analysis results indicate that while both respondents have different focuses and approaches when choosing a partner, they share a common view regarding the importance of core values and emotional support in a healthy relationship.